The determinants of cooperation in buyer-supplier relationships: evidence from certified companies - Milošević, Isidora; Trajković, Ana; Rajić, Tamara; Đorđević, Predrag (Industrija, 2018)
This paper aims to propose and empirically examine an integrated model of the development of cooperation in buyer-seller relationships. Building upon previous research a conceptual model of the relationships between communication, trust, satisfaction with the relationship and relationship commitment and their impact on cooperation has been proposed and empirically examined from the perspective of certified buyers. The application of structural equation modelling on a sample of 186 certified companies operating on Serbian market indicated the antecedent role of communication to trust and the direct impact of trust and commitment on the development of cooperation. Implications of the study have been discussed and limitations and directions for future research are highlighted.
Keywords: buyer-supplier relationships; cooperation; relationship commitment; relationship satisfaction; trust; Communication